Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1590/1807-1929/agriambi.v27n6p447-456
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of crop water status of melon plants in tropical semi-arid climate using thermal imaging

Abstract: The objective of this study was to analyze the feasibility of using thermal images to estimate the water status of melon plants (Cucumis melo L.) in tropical semi-arid climates. The study was conducted in a randomized block design with a split-plot arrangement. The plots comprised of soil cover (with and without mulching), and subplots were constructed using five irrigation regimes (120, 100, 80, 60, and 40% crop evapotranspiration), with five replicates. The following variables were evaluated: canopy temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
1
1
0
Order By: Relevance
“…Biweekly measurements of Ψ Leaf and SMO in melon plants conducted by Aragão et al ( 2023)representing one measurement per phenological phase in the Brazilian semiarid region -demonstrated that the greatest differences between irrigation regimes are observed at 45 DAT, and these differences are more pronounced in soils without dead plant cover, which is consistent with the data presented here. However, when comparing the Ψ Leaf averages obtained here with those observed by Aragão et al (2023), it is noted that the excess irrigation beyond what is required by the crop tends to yield similar results, with a smaller difference (approximately − 0.02 MPa) compared to water de cit (-0.24 MPa), where the difference between de cit treatments in the studies was 10% of ETc. Similarities are observed regarding SMO, thus agreeing with Buckley (2019) regarding the relationship between Ψ Leaf gradients in the soilplant system.…”
Section: Resultssupporting
confidence: 75%
“…Biweekly measurements of Ψ Leaf and SMO in melon plants conducted by Aragão et al ( 2023)representing one measurement per phenological phase in the Brazilian semiarid region -demonstrated that the greatest differences between irrigation regimes are observed at 45 DAT, and these differences are more pronounced in soils without dead plant cover, which is consistent with the data presented here. However, when comparing the Ψ Leaf averages obtained here with those observed by Aragão et al (2023), it is noted that the excess irrigation beyond what is required by the crop tends to yield similar results, with a smaller difference (approximately − 0.02 MPa) compared to water de cit (-0.24 MPa), where the difference between de cit treatments in the studies was 10% of ETc. Similarities are observed regarding SMO, thus agreeing with Buckley (2019) regarding the relationship between Ψ Leaf gradients in the soilplant system.…”
Section: Resultssupporting
confidence: 75%
“…Melon (Cucumis melo L.) is a summer season crop commonly grown for fresh ripe fruit and baby fruit is widely used for pickles in Türkiye (Vural et al, 2000). It is an important alternative crop in arid and semi-arid regions in open-field, where climatic conditions are characterized by drought and low annual rainfall (Aragão et al, 2023). It can be grown under rainfed conditions without irrigation in crop rotation with wheat, barley, and sunflower, while late spring and early autumn frosts limit the vegetation period of melon.…”
Section: Introductionmentioning
confidence: 99%